Объяснение:
1. Преобразуйте в многочлен:
1) (a + 4)²=a²+8a+16 2) (3у - с)²=9y²-6cy+c²
3) (2a - 5)( 2a + 5) =4a²-25 4) (x² + y)( x² - y)=x^4-y²
2. Разложите на множители:
1) 0,36 – с²=(0,6-c)(0,6+c) 2) 5a² + 10a=5a(a+2)
3) 16x² – 49=(4x)²-7²=(4x-7)(4x+7)
3) Упростите выражение: (m - 1)(т + 1) - (т - 3)=mt-2t+m+2
4. Выполните действия:
a) 3(1 + 2xy)( 1 - 2xy) =3(1-4x²y²)=3-12x²y² б) (x²-y)=(x-√y)(a+√y)
5. Решите уравнение: (x - 2)(x + 2) - x(x + 5) = - 8
X²-4-x²-5x=-8
-5x=-4
X=4/5=0,8
а) (а² + 3)(а² – 3) = а⁴ - 9
в) (6 – 5zt)(6 + 5zt) = 36 - 25z²t²
д) (4х + 3у)(–4х + 3у) = -16х²-12ху+12ху+9у²=9у²-16х²
Спростіть вираз:
б) (5 – 2с)(5 + 2с) – 2с(1 – 2с) = 25-4с²-2с+4с²=25-2с
в) а²(а² + 7)(а² – 7) + 49а² = а²(а⁴-49) = а⁶-49а²+49а²=а⁶
Спростіть вираз:
а) (3 – с)(3 + с)(9 + с²) =(9-с²)(9+с²)=81-с⁴
в) (4х – у)(4х + у)(16х² + у²)=(16х²-у²)(16х²+у²)=256х⁴-у⁴
Розв’яжіть рівняння:
б) (2 – 3у)(2 + 3у) = (9у – 2)(2 – у)
4-9у²=18у-4-9у²+2у
20у=4; у=0,2